The Origins and Development of Wilfred Currier Keirstead’s Social and Religious Thought - Goodwin, Daniel C. (Acadiensis, 2008)
W.C. Keirstead was a leading Maritime social scientist, philosopher, and professor at the University of New Brunswick from 1908 to 1944. This article examines the formation of his social thought in an attempt to address the current debate among historians about whether or not social scientists in early-20th-century English Canada embraced modern thought at the expense of their Christian worldview, thereby helping to accelerate secularization. His writings reveal that he was not an agent of secularization, for although Keirstead embraced many aspects of modernity he continued to draw upon the Baptist religion of his youth and maintained a Christian outlook throughout his career. Résumé W.C. Keirstead était un éminent spécialiste des sciences sociales, philosophe et professeur à l’Université du Nouveau-Brunswick de 1908 à 1944. Cet article examine la formation de sa pensée sociale en vue d’éclairer le débat actuel parmi les historiens à savoir si oui ou non les spécialistes des sciences sociales du Canada anglais du début du 20e siècle ont adhéré à la pensée moderne aux dépens de leur vision chrétienne du monde, contribuant ainsi à accélérer la sécularisation. Ses écrits révèlent qu’il n’était pas un agent de la sécularisation, car bien que Keirstead ait souscrit à de nombreux aspects de la modernité, il continua à puiser dans la religion baptiste de sa jeunesse et conserva une perspective chrétienne tout au long de sa carrière.